Aspectos ambientais na contratação de obras públicas - Siqueira, Aretusa dos Santos de (2012)
The present work aims to analyze the environmental aspects in public works contracts conducted through the bidding process, including the bulge in his quest for sustainability, establishing as State obligation to include environmental criteria for economy of natural resources. With its enormous power purchases and hires the State went on to act as a potential economic engine, assuming the responsibility for the formation of new markets more sustainable and ecologically correct, seeking alternatives ranging from recycling, saving water and energy, to the decrease of harmful gases to the environment. Apart from this contribution to the environment through public signings, this research will also analyze the issue of environmental liability in the State about the environmental damage arising from their employment under the auspices of the triple responsibility (civil, administrative and criminal law) provided for in our Magna Carta.